2019
DOI: 10.1002/smll.201905516
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Scale Fabrication of In‐Plane Heterojunctions of Few‐Layer MoS2 via In Situ Scanning Transmission Electron Microscopy

Abstract: Transition metal dichalcogenides (TMDs) have emerged as promising 2D materials that can be atomically thin semiconductors, semimetals, metals, or even superconductors. These materials consist of transition metal atoms sandwiched between two layers of chalcogen atoms. Their innate layered structure stems from the existence of strong intralayer bonding forces and weak interlayer van der Waals interactions. [1] Recently, studies have uncovered a Layered MoS 2 is a prospective candidate for use in energy harvestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…However, with the rapid growth of interest in the optical, electronic, and mechanical properties of TMDCs [17,18], several studies have used in situ scanning transmission electron microscopy (STEM) to document structural transformations under equilibrium conditions [4,[19][20][21]. In addition, some observations of in-situ heterojunction formation and growth have also been made in the same class of materials [22,23]. These nanoscopic investigations have shown that defects and vacancies form due to the application of multiple types of external stimuli, along with the dynamic migration of transition metal and chalcogen atoms towards favourable grain boundary formations [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the rapid growth of interest in the optical, electronic, and mechanical properties of TMDCs [17,18], several studies have used in situ scanning transmission electron microscopy (STEM) to document structural transformations under equilibrium conditions [4,[19][20][21]. In addition, some observations of in-situ heterojunction formation and growth have also been made in the same class of materials [22,23]. These nanoscopic investigations have shown that defects and vacancies form due to the application of multiple types of external stimuli, along with the dynamic migration of transition metal and chalcogen atoms towards favourable grain boundary formations [24].…”
Section: Introductionmentioning
confidence: 99%
“…8(b–e)). 72 With electron beam MoS 2 layer-thinning, a heterointerface between monolayer and few-layer 2D MoS 2 is demonstrated via dark-field STEM (Fig. 8(b)) as manifested by different Moiré patterns.…”
Section: Visualization Of Heterointerfaces In 2d Tmd Layersmentioning
confidence: 99%
“…Given that the location of CVD growth of single-layer MoS 2 is relatively random, understanding its growth mechanism can substantially benefit research on MoS 2 growth. TEM helps elucidate the atomic structure and the chemical composition information of particle evolution during catalysis [34][35][36][37][38][39][40]. The material properties of MoS 2 are preferably a single layer or very few layers.…”
Section: Growth Mechanism Of Mosmentioning
confidence: 99%